Noticia sobre dos nuevas estelas decoradas: las estelas de La Pedrona y del Mesto (Almadén, Ciudad Real) - Blanco Fraga, Ana María; García Bueno, Carmen (Gerión. Revista de Historia Antigua, 2010)
We present two decorated steles found in the municipal term of Almadén (Ciudad Real). They appeared in individual majanos, within the scope of Roman archaeological sites, in both cases. One is a zone where traditionally it's practiced an economy based on agriculture (cerealístico culture) and the cattle ranch, besides the operation of the great mining wealth of its subsoil. This territory is furrowed by several cattle and commercial channels. All this is associate to the presence of diverse settlements from ancient. These two pieces extend the collection of decorated steles until now known in this geographic area, showing their relation with the cultural currents of the Age of Bronze and, perhaps, the Age of Iron I.
Keywords: Almadén (Ciudad Real); Decorated Steles; Steles of the Southwest; Final Bronze and Age of Iron I; Natural Resources; Cattle and Commercial Channels; Anthropomorphic Figures; Schematic Decoration